Family Values in the Movie “A Quiet Place”: A Semiotic Approach - Ayuniantari, Ni Putu; Saptanti, Eunike Iona; Fajarini, Eunike Serfina (Humanis, 2020)
There are only few commercially successful horror movies over fifty years since 1970s that win many awards. One of many horror films released in 2018 that left deep impression for audiences is “A Quiet Place”. McClintock (2018) claimed that the movie has earned more than $300M globally, making strides toward becoming one of the biggest-grossing original scary movies ever. “A Quiet Place” is a silence movie directed by John Krasinski. Because of its silence and quietness, the audiences were forced to focus on the nonverbal signs in the movie. The theme of this movie was family values. One of many important films is mise –en-scene as this communicates indirectly to the audiences. The aim of this study was to know how the theme “Family Values” was visualized in the movie. Using qualitative approach and Semiotics analysis method, this study focused on how the signs and mise-en-scene in the film were interpreted based on the researchers’ interpretation using Metz’ Grand Syntagmatique (1974). This study was a desk research and the data were obtained from selected scenes of the movie. The results showed that there were five syntagma category used in the film; i.e. autonomous shot, episodic sequence, scene, alternate syntagma, and descriptive syntagma. The signs that were presented in the film were arranged by using those five syntagma to show the audience about the family value in the movie.